Core temperature responses to elite racewalking competition - Stevens, C. J.; Ross, M. L.; Périard, J. D.; Vallance, S.; Burke, L. M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: The core temperature responses during exercise and effects of different cooling strategies on endurance performance under heat stress have been investigated in recreational athletes. This investigation aimed to determine peak rectal temperatures during elite racewalking competitions and to detail any cooling strategies used. Methods: Rectal temperature was measured in 14 heat-adapted elite/preelite race walkers (9 females) via a telemetric capsule across 4 outdoor events, including the 2018 Commonwealth Games (race 1: 20 km, 25°C, 74% relative humidity [RH], n=2) and 3 International Association of Athletics Federations-sanctioned 10-km events (race 2: 19°C, 34% RH, n=2; race 3: 29°C, 47% RH, n=14; and race 4: 23°C, 72% RH, n=11). All athletes completed race 3, and a subsample completed the other events. Their use of cooling strategies and symptoms of heat illness were determined. Results: Peak rectal temperatures >40°C were observed in all events. The highest rectal temperature observed during an event was 41.2°C. These high rectal temperatures were observed without concomitant heat illness, with the exception of cramping in one athlete during race 1. The rectal temperatures tended to reach a steady state in the second half of the 20-km event, but no steady state was observed in the 10-km events. The athletes used cooling strategies in race 1 only, implementing different combinations of cold-water immersion, ice-slurry ingestion, ice-towel application, ice-vest application, and facial water spraying. Conclusions: Elite/preelite race walkers experience rectal temperatures >40°C during competition despite only moderate-warm conditions, and even when precooling and midcooling strategies are applied.